PEA organization image and homeland security using CCTV - Ketsupich Thananunsophon; Chavana Pavaganun; Preecha P. Yupapin (My University, 2010)
This paper presents the use of information technology and power line poles in the organization known as Provincial Electricity Authority (PEA), where there are two different applications are described. Firstly, the multi-channel communication (MCC) using both wire and wireless communication media for PEA organization image development is discussed. Secondly, the use of closed circuit television (CCTV) that they can be installed into the street lamps on the power line poles throughout the nation for homeland security is proposed and discussed in details.
Keywords: Homeland; Line (geometry); Power-line communication; Trade Secret Protection Methods